Efeitos da intervenção com vídeo games ativos no equilíbrio de crianças com e sem Transtorno do Desenvolvimento da Coordenação: um estudo follow-up - Draghi, Tatiane Targino Gomes (Universidade Federal de São Carlos, 2023)
General objective: To analyze the static balance of children with and without DCD in bipedal and unipodal positions, and to monitor the effects of training through AVGs, Wii Fit and Xbox Kinect on the balance and postural sway of these children.

Results: Two main studies were developed throughout this doctorate, being the Study I entitled “Short- and long-term changes in balance after active video game training in children with and without Developmental Coordination Disorder: a randomized controlled trial”, and Study II entitled “One-leg stance in children with and without Developmental Coordination Disorder: Convergent validity between CoP descriptors and clinical balance tasks”. Both AVGs, Wii Fit and Xbox Kinect, provided improvement in clinical measures of balance in both groups of children, and this effect was still present after four months. Furthermore, both training were able to modify the sway in the eyes open condition, which corresponds to the demands of the trained task. The training in this study may have provided the opportunity to experience displacement in various directions and speeds, and this may have provided, specifically for children with DCD, opportunities to explore their stability limits. Regarding unipodal support, children with DCD performed worse on balance and postural sway tasks, as verified by clinical tests and the force plate (FP), compared to their peers. In addition, differences between groups were also found for most of the global descriptors, as well as for the structural descriptors of RMS-rambling and RMS-trembling. Significant associations between FP and clinical tasks were high for similar postures such as Yoga-stance and Hug-knee. Relationships between clinical and CoP-derived tasks demonstrated convergent validity for global descriptors.

Conclusion: The results of the two studies contribute to the scientific literature and therapists by pointing out AVGs as a possible therapeutic resource in the treatment of children with DCD, as well as by expanding the understanding of the dynamics of one-leg balance, which may guide the objectives and therapeutic conducts.
Effects of intervention with active video games on the balance of children with and without Developmental Coordination Disorder: a follow-up study
Keywords: Transtorno do Desenvolvimento da Coordenação; Equilíbrio; Crianças; Plataforma de força; Active video games; Developmental Coordination Disorder; Balance; Children; Force Plate; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL